ANALISIS STRATEGI BAURAN PEMASARAN PROSES PENYEWAAN ONDEL-ONDEL PADA SANGGAR SENI BETAWI MAMIT CS DI JAKARTA - Alissa Alissa; Yayak Heriyanto (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aims to determine the marketing mix of the ondel-ondel rental process at the Betawi Art Studio Mamit CS. The method used in thisresearch was a qualitative method, while data collection was done through interviews, observations and document studies. Informants in this study included administrators, event organizers and community leaders. Data analysis techniques used included data validity testing and triangulation, and activities in qualitative data analysis included data reduction, data presentation and conclusion drawing or verification. The results showed that the marketing strategy of the ondel-ondel rental process at the Betawi Art Studio Mamit CS in Jakarta, when viewed based on 7 (seven) indicators of the marketing mix, is in the good category. This can be seen from the analysis of products, which is in good category, prices in good category, promotions in good category, places in poor category, people in good category, physical facilities in poor category,and processes in good category.